QUALITY OF LIFE COMPARATION IN METASTATIC BONE DISEASE PATIENT BEFORE AND AFTER SURGERY IN DR. SOETOMO GENERAL HOSPITAL - Ferdiansyah Mahyudin; Mouli Edward; Muhammad Hardian Basuki; Rizky Agung Satria (Journal Orthopaedi and Traumatology Surabaya)
Background: Metastatic bone disease is bone pathologic process caused by spread of primary tumor. The incidence of metastatic bone disease varies between 20-75% corresponds to the primary site of the malignancy. Surgery in metastatic bone disease aim to cure or palliate the morbidity caused by the disease. Operative treatment could reduce pain, improve function, control metastatic focus of the malignancy, and provide mechanical stabilization. Based on those benefits, operative treatment is important to improve quality of life in patients with metastatic bone disease.